(untitled) (Medical Forum Monthly, 2021)
Objective: This study aims at identifying frequency and distribution of common electrophysiological variants according to age and gender in our region. Study Design: A Cross-sectional study Place and Duration of Study: This study was conducted at the department of Neurology Sheikh Zayed Medical College/Hospital, Rahim Yar Khan from Jan 2015 to October 2020. Materials and Methods: Patients clinically and electro diagnostically diagnosed as GBS in the last five years were included in the study. After using the electro diagnostic criteria, patients were categorized into three main variants: AMSAN (acute motor-sensory axonal neuropathy), AMAN (acute motor axonal neuropathy), and AIDP (acute inflammatory demyelinating polyneuropathy). Results: 180 patients included in the study of which 62.22% were male and 37.78% were females. About 28.33% had AMSAN, 32.78% had AMAN, and 31.11% had AIDP, respectively. Males are affected more in each type. There was not much difference in the incidence of different variants in our region. Conclusion: Different variants of GBS occur with slight variation in incidence depending upon the criteria used to classify as axonal or demyelinating variety.